Plug-in hybrid electric vehicle observed utility factor: Why the observed electrification performance differ from expectations. Issue 2 (1st February 2022) - Raghavan, Seshadri Srinivasa; Tal, Gil
Abstract: Plug-in hybrid electric vehicles (PHEVs) are an effective vehicle technology to reduce light duty vehicle greenhouse gas emissions and gasoline consumption. They combine all-electric driving capabilities of a battery electric vehicle with the engine downsizing and fuel economy improvements of a hybrid electric vehicle. Their environmental performance is predicated upon the metric utility factor (UF). It is formally defined in the Society of Automotive Engineers J2841 standard and denotes the fraction of vehicle miles traveled (VMT) on electricity (eVMT). Using year-long driving and charging data collected from 153 PHEVs in California with 11–53 miles range, this article systematically evaluates what aspects of driving and charging behavior causes observed UF to deviate from J2841 expectations. Our analyses indicated that charging behavior, distribution of daily VMT, efficiency of electrical energy consumption in the charge depleting (CD) mode, and annual VMT were the major factors contributing to the disparities between observed and expected UF. The direction and magnitude of their individual effect varied with the vehicle type and range. Approximately ±45% of deviations from J2841 UF is attributable to the observed charging behavior. Differences in daily VMT distribution were responsible for −20% to +3% of deviation. Annual VMT and effective CD range achieved on-road influenced the UF deviation by ±25% and −20% to −4%, respectively.